Psychological Bases of Formation of Key Economical Information Technology Specialist Competencies of Higher Education - Lyubashits, Valentin Y.; Shirshov, Alexei A.; Lopukhinskiy, Leonid M.; BondÐ°rÐµvÐ°, TÐ°tyÐ°nÐ° O.; Khizbullin, Faiz F.; Stratonova, Lydia M. (International Review of Management and Marketing, 2016)
The article presents the economic and social changes in society related to computerization and the inclusion of new economical information technologies in all spheres of life that pose new challenges with respect to the determination of the content of economical-technological preparation of the future economist at the Institute, as well as the psychological aspects of the formation of the key information and economical-technological competence at the Institute in stages starting with the creation of his project. The article analyzes the literature on the subject, set forth the means and methods of educational process at different levels, the conditions and the content of education specialist of the profile elements and levels of formation of key information technology competencies opinion on the appropriateness and necessity of the use of new information technologies as a means of improving the quality of learning process. Keywords: psychology, economical-technological competence, information-technological competence JEL Classifications: A20; H70; I20